PERAN PONDOK PESANTREN DAN BOARDING HOUSE DALAM PEMBENTUKAN AKHLAK MAHASISWA UIN SULTAN MAULANA HASANUDDIN BANTEN - Dadeng Juhana (QATHRUNÂ, 2020)
The purpose of this study was to describe the role of Islamic boarding schools and boarding houses in the moral formation of a student, efforts to instill good character towards students, and to supervise students in social interaction and social interaction. The method used in this research is descriptive method with a qualitative approach. Data collection techniques with interviews, observation and documentation as supporting data. The analysis technique is performed by data reduction, data presentation, data validity by triangulation and drawing conclusions or verification. The results of this study 1) the pattern of moral development of students at the Al-Mustajib Madarijul 'Ulum Islamic boarding school, namely by various methods including: Uswah method (exemplary), moral habituation method, ethical method, bandungan method, and language method, 2) strategic role of Islamic boarding schools Al-Mustajib madarijul in an effort to form morals, including through effective programs such as: carrying out muhadoroh activities where students learn to give speeches or preach, carry out prayers five times in congregation, carry out night prayers, and memorize the Al-Qur'an and read the yellow book, 3 ) The experience gained at the Al Mustajib Madarijul 'Ulum Islamic boarding school is the basis for how they practice moral knowledge in their daily life, both in terms of speaking, dressing and socializing. The experience gained at the boarding house wisma jaya is implemented with social skills such as dressing with covering your genitals and socializing in an Islamic manner by paying attention to the ethics and norms that apply in society.